2017
DOI: 10.1091/mbc.e17-05-0335
|View full text |Cite
|
Sign up to set email alerts
|

Sphingolipids facilitate age asymmetry of membrane proteins in dividing yeast cells

Abstract: Asymmetrically dividing yeast cells segregate determinants of aging, and sphingolipids play a role in restricting the diffusion, and thus the mixing, of young and aged plasma membrane proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 72 publications
3
23
1
Order By: Relevance
“…This does not appear to stem from unusual features of the proteins themselves, as similar proteins targeted to a yeast vacuolar membrane or a mammalian plasma membrane are far more mobile (D~0.1 µm 2 /s) [11]. Consistent with the cited studies, FRAP experiments on a variety of other membrane proteins detected very little recovery on 10 min timescales, in fission yeast as well as budding yeast [13][14][15]. Thus, it appears that yeast plasma membranes severely restrict diffusion of embedded proteins.…”
Section: Slow Diffusion Restricts Mobility In the Yeast Plasma Membranesupporting
confidence: 70%
See 1 more Smart Citation
“…This does not appear to stem from unusual features of the proteins themselves, as similar proteins targeted to a yeast vacuolar membrane or a mammalian plasma membrane are far more mobile (D~0.1 µm 2 /s) [11]. Consistent with the cited studies, FRAP experiments on a variety of other membrane proteins detected very little recovery on 10 min timescales, in fission yeast as well as budding yeast [13][14][15]. Thus, it appears that yeast plasma membranes severely restrict diffusion of embedded proteins.…”
Section: Slow Diffusion Restricts Mobility In the Yeast Plasma Membranesupporting
confidence: 70%
“…Mutations that perturb the normal lipid composition of the plasma membrane can modestly increase protein diffusion [11,15]. Thus, an unusual lipid composition may increase membrane viscosity, hence slowing diffusion.…”
Section: Why Is Diffusion So Slow In the Yeast Plasma Membrane?mentioning
confidence: 99%
“…S7A and movie S9) ( 48 ). Using a microfluidic device to observe repeated budding cycles of single mother cells ( 49 ), we found that DUMP were asymmetrically retained in mother cells through most of the RLS ( Fig. 5B and movie S10).…”
Section: Resultsmentioning
confidence: 99%
“…4 and SI Appendix, Fig. S2C) but also posttranslational protein modification (39) and the lipid composition of the PM (40). Additionally, a range of protein aggregates that are formed by cellular stress or aging tend to be retained in mother cells (7,41).…”
Section: Discussionmentioning
confidence: 99%